The evolution of regulatory strategies in relation to nicotine products and their implications for product innovation and harm reduction - Rooke, Catriona (2011)
The current "smoking epidemic" is a global problem for governments and organisations concerned with public health. Recently, this problem has been conceptualised as one of regulation. Within the tobacco control community, there has been growing concern that the division of regulatory responsibility for conventional tobacco products (i.e. cigarettes, cigars, pipe tobacco) and alternative modes of nicotine delivery (nicotine replacement therapy products such as gums, patches and inhalers) is having adverse effects on the innovation of new medicinal products and on providing smokers with acceptable alternatives to cigarettes, the most harmful and widely used nicotine product. The 'alternatives' are mainly regulated as pharmaceuticals; therefore, must reach safety standards comparable with those required for medications rather than being compared with the known harm caused by tobacco smoking. Whilst a number of commentary and position pieces have discussed this problem, there has been little empirical work on how the current UK regulatory set-up evolved and what impacts it has.